Development of Professional Competency for Printing Quality Control Personnel Using Training System via Edmodo - Wat Ploysri; Chantana Viriyavejakul (My University, 2019)
Abstract This study aimed to solving problems in providing printing quality control personnel to Thai printing industry. The problems which are mainly concerned including: (1) the lack of competency and ability in authentic performance as well as (2) the lack of capacity in following the professional standard. Therefore, the study employs Edmodo to facilitate the training system. The research procedures included these following processes: (1) reviewing literature, (2) Exploring and evaluating the needs, (3) developing the training system prototype, (4) Evaluating the conceptual framework developed, (5) Drafting the training package through Edmodo, (6) evaluating and Implementing the training system, and (7) Taking the result into improving. The result elucidated that the developed PQC-Training system, after being applied into creating the training package by using the Edmodo website and application, could effectively promote the trainees’ professional competency that was in accordance to requirements of organizations in Thai printing industry.
Keywords: Training System; Educational Games and Gamification